Application of the image processing technique in identifying the particle dispersion from a centrifugal fertilizer spreader. (3rd September 2017) - Chen, Wei; Williams, Kenneth C.; Donohue, Timothy J.; Katterfeld, Andre
ABSTRACT: Particle dispersion in the vicinity of an agricultural fertilizer spreader is difficult to capture due to the rapid particle traveling motion. This paper introduced a granule impact indentation-based technique to simultaneously record the two-dimensional particle dispersion from a spinning concave disc type of spreader. A Nitrogen-Phosphorus-Potassium (NPK) type of fertilizer was utilized to induce indentations on aluminum foils placed on the wall panels confining an experimental spreader system. Subsequently, an image processing technique which is comprised of the multicolor edge detection, the curve closing, and the region merging techniques was purposely developed to automatically identify and locate the granule impacts on the sampled foil digital images. Overlapping impacts were characterized based on the granulometry of the fertilizer sample. The reconstructed particle dispersion pattern using the image processing method showed good agreement with the experimental observations. The outcome of this research enabled a fast and effective method for quantitatively assessing the particle distribution for a specific fertilizer spreader.